"A complex interface: Exploring sickle cell disease from a parent's perspective, after moving from Sub-Saharan Africa to North America". (17th November 2018) - Aiko Bruce, Aisha; Witol, Adrienne; Alvadj-Korenic, Tatjana; Mayan, Maria; Greenslade, Haley; Plaha, Mandeep; Venner, Mary Anne
Abstract: Introduction: Sickle cell disease (SCD) is an inherited, multi-system, chronic disease with the highest prevalence affecting people of Sub-Saharan African descent. While major advances in SCD care have occurred over the last few decades in many African countries these advances are not readily available. Prior literature from Ghana and Kenya describe stigma, despair, and economic burden as well as hope when a child has SCD. When people migrate to North America with a child with SCD it is unknown whether their perception of the disease changes. We asked, "How do immigrant parents of children with SCD from Sub-Saharan Africa perceive, and manage the disease in the context of western medical care?" Methods: The research question was explored with qualitative methodology, specifically focused ethnography. Semi-structured interviews were conducted with parent(s). The interviews were audio recorded, transcribed, and open coded. Rigor was determined through methodological coherence, appropriate and sufficient sampling, and iterative data collection and analysis. Results: Twelve interviews were conducted. Identified themes are as follows: memories of SCD in Africa, the emotional journey towards acceptance, and parental approach to care for their child. Conclusions: Healthcare providers should be responsive to an immigrant families' needs and not expect linear progression of emotional acceptance to the diagnosis. Healthcare providers patience with the process helps establish trust, works to facilitate and encourage hope and acknowledges the strength of the families, and their dedication to their family member. Healthcare providers should acknowledge parents' sources of support (religion/family) and ensure parents are aware of medical advances.